2019
DOI: 10.4236/jmf.2019.94031
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Power Series Method to Numerically Approximate Contingent Claim Partial Differential Equations

Abstract: We introduce a previously unused numerical framework for estimating the Black-Scholes partial differential equation. The approach, known as the Power Series Method (PSM), offers several advantages over traditional finite difference methods. Our objective is to highlight the advantages of the PSM over traditionally used numerical approximation approaches. To meet this we deploy a numerical approximation scheme to illustrate the PSM. The PSM is more stable than explicit methods and thus computationally more effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Buetow and Sochacki [1] demonstrated that PSM can be used to efficiently solve and analyze the forward linear BS options model and is comparable to the explicit finite difference method and the Crank-Nicolson method. Matić, Radoičić and Stefanica [47] show that PSM can be used to efficiently solve the inverse problem for determining the implied volatility in the linear BS options model.…”
Section: Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Buetow and Sochacki [1] demonstrated that PSM can be used to efficiently solve and analyze the forward linear BS options model and is comparable to the explicit finite difference method and the Crank-Nicolson method. Matić, Radoičić and Stefanica [47] show that PSM can be used to efficiently solve the inverse problem for determining the implied volatility in the linear BS options model.…”
Section: Modelmentioning
confidence: 99%
“…As in [47], we use auxiliary variables and power series to solve this nonlinear BS options model. In the appendix, we give the symbolic solution for this model similarly to how it was done in [1]. As in [1] and Glover, Duck, Newton [48], we approximate the pay off with a smooth function.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations